Causality between External Debt and Capital Flight in Sub-Saharan Africa - Fofack, Hippolyte (2012)
Over the past few decades, the foreign liabilities of the majority of countries in Sub-Saharan Africa have grown dramatically, propelling most nations into the status of Highly Indebted Poor Countries, when these liabilities reached unsustainable levels in the 1990s. At the same time, increases in capital flight from the region followed a parallel trend, leading scholars to draw on "revolving door" models to explain the apparent positive covariation of external debt and capital flight in the region. This paper investigates the causality between external debt and capital flight in a cross-section of Sub-Saharan African countries using co-integration and error-correction models. Although dual causality, which is consistent with the revolving door hypothesis, cannot be rejected for the majority of countries, empirical evidence highlights the lead of external debt over capital flight. The significance of error-correction terms points to a long-run co-integrating relationship between external debt and capital flight in a large number of countries.